Effect of Problem Based Instruction on Higher Other Thinking Skills - Nurussaniah Nurussaniah; Reo Ramandha (Prosiding SNFA (Seminar Nasional Fisika dan Aplikasinya), 2016)
This study investigated how the problem based instruction influenced higher other thinking skills. One group pretest-postest design was used in this study. 36 student from science class participated in this study. Data in this study were collected using essay test. The result of Wilcoxon match pairs Test indicated that there are effects of problem based instruction to higher other thinking skills. This suggest that the Problem Based Instruction had a significant effect on increasing the higher other thinking skills. Keywords:  problem based instruction, higher other thinking skills